2014
DOI: 10.1016/j.jchromb.2013.12.039
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput quantification method of curcuminoids and curcumin metabolites in human plasma via high-performance liquid chromatography/tandem mass spectrometry

Abstract: Curcuminoids, a mixture of curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC), have shown a variety of clinical benefits for several human chronic diseases including osteoarthritis, rheumatoarthritis, and type II diabetes. However, the oral bioavailability of curcumin is extremely low due to its avid metabolism to curcumin O-glucuronide (COG), curcumin O-sulfate (COS), tetrahydrocurcumin (THC), and other minor metabolites. This paper reports a unique liquid chromatography/tandem mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 8 publications
3
48
0
Order By: Relevance
“…Positive ionization mode delivered different fragmentation patterns: for curcumin, the listed m/z signals were recorded: 391, 369, 285, 253, 177, 161, 145, and 117; for DMCC: 361, 339, 255, 223, 177, 147, 145, 131, and 117; and for BDMCC: 331, 309, 225, 189, 147, 131, and 117. The general fragmentation patterns of curcuminoids obtained in this study were in agreement with those previously reported by Cao, Xu, and Liu () and Jiang Soogyi, Jacobsen, Timmermann, and Gang (). However, the MS/MS spectra recorded by the authors using the Q‐TOF analyser revealed the presence of a higher number of fragments, which helped in the identification of these compounds.…”
Section: Resultssupporting
confidence: 92%
“…Positive ionization mode delivered different fragmentation patterns: for curcumin, the listed m/z signals were recorded: 391, 369, 285, 253, 177, 161, 145, and 117; for DMCC: 361, 339, 255, 223, 177, 147, 145, 131, and 117; and for BDMCC: 331, 309, 225, 189, 147, 131, and 117. The general fragmentation patterns of curcuminoids obtained in this study were in agreement with those previously reported by Cao, Xu, and Liu () and Jiang Soogyi, Jacobsen, Timmermann, and Gang (). However, the MS/MS spectra recorded by the authors using the Q‐TOF analyser revealed the presence of a higher number of fragments, which helped in the identification of these compounds.…”
Section: Resultssupporting
confidence: 92%
“…These compounds had one carbonyl connected with a methylene (O C-CH 2 -) in their structures. Their characteristic fragmentation behaviors often took place in ˛ or ˇ-position of carbonyl group [40] (take 6-gingerol as an example, Fig. 3J).…”
Section: Identification Of Gingerolsmentioning
confidence: 99%
“…8 Biochemically, the curcuminoids comprise curcumin, demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC), 9 and in soluble form generally exist as keto-enol tautomers. 10 Pharmacologically, curcuminoids have been reported to possess significant anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%